1993
DOI: 10.1038/jcbfm.1993.35
|View full text |Cite
|
Sign up to set email alerts
|

Role of Nitric Oxide in the Cerebral Vasodilatory Responses to Vasopressin and Oxytocin in Dogs

Abstract: Summary:We angiographically assessed the vasodilatory effects of vasopressin and oxytocin on the basilar arteries in dogs. Intracisternal bolus injections of vasopressin (100 pmol and 1 nmol) and oxytocin (1 and 10 nmol) produced dose-dependent increases in the internal diameter of the basilar arteries without affecting mean arterial blood pres sure. The maximal dilatations of the basilar arteries in duced by 1 nmol vasopressin and 10 nmol oxytocin were 142.3 ± 19.9 and 136.8 ± 25.5% of the baseline, respec ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
2

Year Published

1995
1995
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(36 citation statements)
references
References 28 publications
1
33
0
2
Order By: Relevance
“…73 Less vasoconstriction in coronary and cerebral circulations may be due to the additional NO-mediated vasodilating effect of vasopressin on these circulations. 74,75 The effects of vasopressin on the heart (reduced cardiac output and heart rate) are mainly due to increased vagal tone and decreased sympathetic tone as well as a decrease in coronary blood flow at high circulating levels of vasopressin. 10 Of relevance to septic shock, vasopressin enhances the sensitivity of the vasculature to other pressor agents.…”
Section: Vasoconstrictor Effectsmentioning
confidence: 99%
“…73 Less vasoconstriction in coronary and cerebral circulations may be due to the additional NO-mediated vasodilating effect of vasopressin on these circulations. 74,75 The effects of vasopressin on the heart (reduced cardiac output and heart rate) are mainly due to increased vagal tone and decreased sympathetic tone as well as a decrease in coronary blood flow at high circulating levels of vasopressin. 10 Of relevance to septic shock, vasopressin enhances the sensitivity of the vasculature to other pressor agents.…”
Section: Vasoconstrictor Effectsmentioning
confidence: 99%
“…In the majority of blood vessels, application of CGRP has been reported to cause dilation through an endothelium-independent process. These vessels include cat cerebral (16,48), rat mesenteric (1,20,25,35), rat stomach mucosal (27), rabbit jejunal (34), dog basilar (40), dog lingual (33), and human uterine arteries (5). A primary signal transduction pathway involved in this form of CGRP activation is adenylate cyclase, which increases cAMP and cAMP-dependent protein kinase (PKA)-activating K ϩ channels including ATP-sensitive K ϩ (K ATP ϩ ) channels (37,38,41).…”
mentioning
confidence: 99%
“…Third, we determined whether nitric oxide (NO) plays a role in mediating oxyto cin-induced arteriolar dilation. Recent evidence indicates that dilator prostaglandin effects are mediated via a NO mechanism in newborn pigs [23], and other investigators have shown that inhibition of nitric oxide synthase (NOS) eliminates cerebral hyperemia to oxytocin [12], Fourth, we determined the role of ATP-sensitive potassium chan nels (K atp) in mediating cerebral arteriolar dilation to oxytocin. We have shown that KATp-mediated cerebral arteriolar dilation is virtually eliminated following isch emia [3].…”
Section: Introductionmentioning
confidence: 99%